2016
DOI: 10.1021/acs.analchem.6b00365
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Self-Referencing Approach to Whispering Gallery Mode Biosensing and Its Application to Measurement within Undiluted Serum

Abstract: The new agreement specifically addresses what authors can do with different versions of their manuscript -e.g. use in theses and collections, teaching and training, conference presentations, sharing with colleagues, and posting on websites and repositories. The terms under which these uses can occur are clearly identified to prevent misunderstandings that could jeopardize final publication of a manuscript (Section II, Permitted Uses by Authors).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 39 publications
(89 reference statements)
0
18
0
1
Order By: Relevance
“…However, it comes at a significant cost in terms of refractive index sensitivity. We have previously shown that uncoated fluorescent and lasing microspheres can be used to routinely detect specific biomolecules down to few ng/mL concentrations, even in undiluted human serum [ 6 , 18 ]. Therefore, despite the significant reduction of both the refractive index sensitivity and Q-factor, we believe that such a platform would still be useful for a large range of biosensing applications where the target concentration ranges from hundreds of pg/mL to ng/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it comes at a significant cost in terms of refractive index sensitivity. We have previously shown that uncoated fluorescent and lasing microspheres can be used to routinely detect specific biomolecules down to few ng/mL concentrations, even in undiluted human serum [ 6 , 18 ]. Therefore, despite the significant reduction of both the refractive index sensitivity and Q-factor, we believe that such a platform would still be useful for a large range of biosensing applications where the target concentration ranges from hundreds of pg/mL to ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The optical wave circulating along the resonator’s inner surface generates optical resonances, whose spectral positions are strongly dependent on the refractive index contrast between the resonator and its surrounding environment as well as the resonator’s shape [ 1 ]. This distinctive feature of WGMs, combined with their extremely high quality factor (Q-factor), defined as the ratio between the resonance wavelength and its full width at half maximum (FWHM), in addition to the small mode volume possible, have enabled WGM resonators to become prime candidates for highly sensitive, label-free bio-chemical sensors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. WGM based sensing mechanisms, such as (1) resonance spectral position shifts [ 3 , 4 , 5 , 6 , 7 ], (2) linewidth broadening/Q-factor spoiling of the resonances (e.g., due to stress-induced geometry deformation [ 8 , 9 ] or dissipative interaction [ 10 , 11 , 12 ]), and (3) splitting of the two counter-propagating WGMs [ 13 , 14 ], have been extensively researched.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the system in which WGM resonators are equipped, advances such as transduction and data-processing or filtering techniques [ 21 ], dynamic referencing [ 111 ], surface functionalization [ 112 , 113 , 114 ], and the integration of microfluidics have been reported. Many WGMs are integrated into microfluidic chips to streamline testing with a small sample volume [ 104 ].…”
Section: Whispering Gallery Mode (Wgm)-based Biosensorsmentioning
confidence: 99%
“…These are typically based on microbubbles, microspheres, or microdroplets. Some notable modifications were label-free surface functionalization [ 120 , 123 , 137 , 138 ], doping [ 118 , 119 ], and self-referencing [ 111 , 120 ].…”
Section: Whispering Gallery Mode (Wgm)-based Biosensorsmentioning
confidence: 99%